Impact of European Union Assocation Agreements on Mediterranean Countries - Ghesquiere, Henri (IMF Working Papers; Working Paper, 1998)
By establishing free trade for industrial products in 12 years, the European Union's Association Agreements with countries in the Mediterranean region seek to promote accelerated economic growth. This paper reviews the literature and evaluates the economic benefits and costs for Tunisia, Morocco, Lebanon, Egypt, and Jordan. It concludes that the benefits could be substantial, but only if accompanied by deep supplementary reforms, including extending trade liberalization to services and agriculture and on a multilateral basis, improving the environment for foreign direct investment, ensuring an adequate fiscal and exchange rate policy response, and strengthening European Union assistance.